Analysis Of Income And Feasibility Of Rice Farming Before And During Covid-19 In Seram Utara Timur Kobi Sub-District - Miranti lelapratiwi; Ir. M Turukay, SP, MSs; J.M Luhukay, SP,MSc (International Journal of Economics, Business and Innovation Research, 2023)
Lowland rice is a source of life for humans where most of the rice is processed as rice which is a source of energy consumed by many people, especially Indonesia. The purpose of this study was to analyze income, eligibility, land rent and factors that affected income during the Covid-19 pandemic in Morokay Village. This research was conducted in Morokay Village, North Seram District, East Kobi with a total of 42 rice farmers as respondents. The data collected was then analyzed quantitatively (income, eligibility, land rent and multiple linear regression tests) using Excel and then explained qualitatively. The results of the study showed that the average income before Covid-19 for lowland rice farmers was IDR 10,562,107.64 per planting season. During Covid-19, the income of paddy rice farmers was Rp. (-914,664.95) per growing season. The feasibility results before and during the pandemic had an R/C ratio of 2.55 and 0.86. R/C aims to make production before the pandemic feasible, while during the pandemic it was not feasible. Income results based on rice field farmers' land rent before and during the Covid-19 pandemic amounted to Rp. 2,720,988.19 and Rp (-827,178.476) which shows that before the pandemic it was still feasible because the income was greater than land rent of Rp. 2,000,000 per planting season, while during the pandemic, renting land is not suitable for farming because income is less than renting land. Factors that affect farmers' income are the production and cost of pesticides.